Observation of Unexplained Cases of Unilateral Upper Eyelid Retraction from Idiopathic Inflammation or an Atypical Form of Gravesʼ Orbitopathy - Schuh, Anna; Bayerl-Löhe, Katharina; Hintschich, Christoph (Klinische Monatsblätter für Augenheilkunde, 2024)
Background We observed cases of unilateral upper eyelid retraction (UER) with unclear pathogenesis, where a definitive diagnosis of Gravesʼ orbitopathy (GO) could not be made and other pathologies were ruled out. The aim is to present patientsʼ findings, discuss possible underlying mechanisms, and to describe diagnostic testing and therapeutic approaches.Patients and Methods Patients were retrospectively analyzed who presented to the Department of Ophthalmology of LMU Munich between 2016 and 2021 without a definitive diagnosis of GO or other pathological causes.Results Thirteen patients with unexplained UER were included; all showed thickening of the levator complex in imaging. When biopsy was performed, no malignancy could be detected. Therapeutic strategies included oral steroids and surgical upper eyelid blepharotomy.Conclusion As regards to pathogenesis, in 7/13 patients, a condition of idiopathic UER due to an idiopathic inflammatory response can be postulated rather than a variant of GO.
Keywords: unilateral upper eyelid retraction; idiopathic inflammation; Gravesʼ orbitopathy